2017
DOI: 10.1038/s41598-017-02831-9
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus E7 oncoprotein abrogates the p53-p21-DREAM pathway

Abstract: High risk human papilloma viruses cause several types of cancer. The HPV oncoproteins E6 and E7 are essential for oncogenic cell transformation. E6 mediates the degradation of the tumor suppressor p53, and E7 can form complexes with the retinoblastoma pRB tumor suppressor. Recently, it has been shown that HPV E7 can also interfere with the function of the DREAM transcriptional repressor complex. Disruption of DREAM-dependent transcriptional repression leads to untimely early expression of central cell cycle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 61 publications
4
45
0
Order By: Relevance
“…Thus, the effect of HPV E6/E7 on TMPOP2 expression might be mediated by cellular transcription factors. It was previously shown that high-risk HPV E6 cooperates with E6AP to promote p53 degradation and that HPV E7 impairs the repressive activity of the p53-p21-DREAM pathway (20), which consequently alter the expression of p53 target genes. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the effect of HPV E6/E7 on TMPOP2 expression might be mediated by cellular transcription factors. It was previously shown that high-risk HPV E6 cooperates with E6AP to promote p53 degradation and that HPV E7 impairs the repressive activity of the p53-p21-DREAM pathway (20), which consequently alter the expression of p53 target genes. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3a). The HPV16 oncoprotein E7 disrupts the p53-DREAM repressor complex, thereby resulting in the upregulation of several cell cycle-related genes and abrogation of p53-mediated cell cycle control (27,28). For the common genes, protein interaction For microarray analysis of each tissue type, three primary cell lines and three HPV16-transformed cell lines were used to grow rafts.…”
Section: Resultsmentioning
confidence: 99%
“…Since MYBL2 itself is a DREAM target gene, this might create a positive feedback loop in which B-Myb overexpression drives further B-Myb expression and perpetuates DREAM disruption. 46 This is also relevant to HPV-positive cancers with E7-mediated DREAM complex disassembly. [46][47][48][49][50] Indeed, T98G cells expressing viral oncoproteins have higher amounts of B-Myb and MMB as compared to cells with intact DREAM.…”
Section: Discussionmentioning
confidence: 99%
“…46 This is also relevant to HPV-positive cancers with E7-mediated DREAM complex disassembly. [46][47][48][49][50] Indeed, T98G cells expressing viral oncoproteins have higher amounts of B-Myb and MMB as compared to cells with intact DREAM. 51,52 B-Myb was also identified as a target for E7-mediated transcriptional activation, leading to inappropriate expression of B-Myb in G1 and higher steady state levels in cycling cells, mimicking our model of B-Myb overexpression.…”
Section: Discussionmentioning
confidence: 99%